The crystal structure of bis(selenocyanato-κ1 N)-bis(methanol)-bis((1E,2E)-1,2-bis (1-(pyridin-4-yl)ethylidene)-hydrazine)iron(II) methanol solvate, C34H44FeN10O4Se2 - Li Yue; Hao Liantao; Guo Shibing; Meng Qing-Guo (Zeitschrift für Kristallographie - New Crystal Structures)
C34H44FeN10O4Se2, monoclinic, C2/c (no. 15), a = 26.6523(15) Å, b = 7.6259(3) Å, c = 21.3645(11) Å, β = 117.888(7)°, V = 3838.0(4) Å3, Z = 4, R gt(F) = 0.0336, wR ref(F 2) = 0.0748, T = 293 K.